Spirochetes in the Liver: An Unusual Presentation of a Common STI - Natasha Narang; Layth Al-Jashaami; Nayan Patel (Case Reports in Medicine)
It is estimated that 10% of patients with secondary syphilis have liver enzyme elevations, but clinical hepatitis is rare. However, in HIV-positive patients, syphilitic hepatitis may be much more common. We report a case of a 67-year-old male who developed progressively elevated liver enzymes, followed by development of neurological symptoms and then rash. Though the timeline of his symptom development was unusual, his constellation of symptoms prompted an RPR and FTA-ABS which returned reactive. He was additionally found to be HIV positive with a CD4 count of 946. He was treated with IV Penicillin, and his hepatitis improved thereafter.